2013
DOI: 10.1177/1933719112452941
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Bevacizumab, Sorafenib, and Retinoic Acid on Rat Endometriosis Model

Abstract: Blood vessels are necessary for development and maintenance of the endometriosis and blood flow supplies oxygen and essential nutrient to the disease. Local angiogenesis is regulated by vascular endothelial growth factor (VEGF) and inhibitors of VEGF may be a novel therapeutic approach. We inducted endometriosis in 43 rats and they were randomly allocated into 4 groups. The rats in group I (control n = 11) were given no medication. The rats in group II (n = 11) were given bevacizumab. The rats in group III (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 34 publications
3
43
0
4
Order By: Relevance
“…We chose the number of follicles as the outcome measure. There were 5 experiments that reported the number of follicle alteration after administrating the agents [22, 28]. Taken together, angiogenesis inhibition therapy had no obvious effect on follicle number (SMD –0.78, 95% CI –1.65 to 0.09; P = 0.08) and the heterogeneity was high (I 2 = 71.3%, 95% CI 27% to 89%; H 2 = 2.49; Fig 3).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We chose the number of follicles as the outcome measure. There were 5 experiments that reported the number of follicle alteration after administrating the agents [22, 28]. Taken together, angiogenesis inhibition therapy had no obvious effect on follicle number (SMD –0.78, 95% CI –1.65 to 0.09; P = 0.08) and the heterogeneity was high (I 2 = 71.3%, 95% CI 27% to 89%; H 2 = 2.49; Fig 3).…”
Section: Resultsmentioning
confidence: 95%
“…Endometriosis score outcomes after anti-VEGF/VEGFR therapy were reported in 9 experiments [20, 22, 23, 2628]. Taken together, these experiments showed that anti-angiogenesis intervention was associated with a lower endometriosis score (SMD –1.17, 95% CI –1.65 to –0.69; P < 0.0001) with a large heterogeneity in the estimates (I 2 = 50.3%, 95% CI 0% to 77%; H 2 = 1.01; Fig 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, sorafenib (Nexavar®, Bayer/Onyx Pharmaceuticals), another multikinase inhibitor that interferes with VEGF-R2, VEGF-R3, B-Raf and other tyrosine kinase receptors, was highly efficient in a rat model of induced endometriosis. 57 Despite the risk of cumulative toxicity that cannot be neglected, the concept of combined pathway targeting opens up perspectives for improved control of endometriosis.…”
Section: Pro-angiogenic Signaling Blockersmentioning
confidence: 99%
“…In contrast, there are interesting novel reports that describe ovarian reserve; the number of primordial follicles can be increased by stimulation of RA gene 8, and this occurs without changes in follicle growth activation or atresia [11]. Other authors claimed that RA may activate the reproductive capacity in Wistar albino rats, and they detected significantly high ovarian reserve in rats receiving RA, concluding that RA might be an anti-aging agent [12]. There are some rising concerns about the use of isotretinoin in young girls and particularly in women aged 35 years or more who are willing to have a baby with depleted ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%